Update on the Treatment of Medullary Thyroid Carcinoma in Patients with Multiple Endocrine Neoplasia Type 2 - Ilanchezhian, Maran; Khan, Sophia; Okafor, Christian; Glod, John; Del Rivero, Jaydira (Hormone and Metabolic Research, 2020)
Medullary Thyroid Carcinoma (MTC) is a rare neuroendocrine cancer that accounts for 1–2% of thyroid cancers in the United States (U.S.). While most cases are sporadic, 25% of MTC cases are hereditary. These hereditary cases occur in the setting of Multiple Endocrine Neoplasia Type 2A (MEN2A) or 2B (MEN2B) driven by mutations in the Rearranged during Transfection RET proto-oncogene. This article discusses hereditary MTC in the setting of MEN2 and the treatment options available for it. The first line treatment for this disease is typically a total thyroidectomy and tyrosine kinase inhibitors. Two tyrosine kinase inhibitors, vandetanib and cabozantinib, have been approved for treatment of advanced MTC, but options beyond those are limited. However, several promising treatments are being studied, which are discussed in this review.
Keywords: metastatic MTC; calcitonin; tyrosine kinase inhibitors; clinical trials